2004
DOI: 10.1136/bmj.38236.646678.55
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire survey on use of placebo

Abstract: Objectives To gauge the frequency and circumstances of use of placebo in clinical practice and the attitudes towards its use among those who administer it. Design Retrospective questionnaire. Setting Two large hospitals and various community clinics in the Jerusalem area. Participants 31 physicians working in hospital inpatient and outpatient departments, 31 head nurses working in hospital inpatient departments, and 27 family physicians working in community clinics. Main outcome measures Self report of frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
116
0
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 9 publications
(10 reference statements)
8
116
0
7
Order By: Relevance
“…However, it can be certainly concluded that there is high prevalence of placebo use in clinical practice. Consistent with previous studies, [2,5] this study also found that most of the doctors believed that the effect of placebo was attributable to a psychological mechanism. …”
supporting
confidence: 81%
See 4 more Smart Citations
“…However, it can be certainly concluded that there is high prevalence of placebo use in clinical practice. Consistent with previous studies, [2,5] this study also found that most of the doctors believed that the effect of placebo was attributable to a psychological mechanism. …”
supporting
confidence: 81%
“…With 27% of the GPs reporting daily use of placebo, this group seems to be the highest placebo user, possibly due to reasons like limited diagnostic skills, giving in to patients' demands, etc. Frequent use of placebo as a diagnostic tool (32.2%), a Þ nding consistent with that of an Israel study, [2] can be potentially harmful to patients.…”
mentioning
confidence: 65%
See 3 more Smart Citations